Comparison of digital and film chest radiography for detection and medical surveillance of silicosis in a setting with a high burden of tuberculosis. Issue 3 (6th December 2017) - Franzblau, Alfred; teWaterNaude, Jim; Sen, Ananda; d'Arcy, Hannah; Smilg, Jacqueline S.; Mashao, Khanyakude S.; Meyer, Cristopher A.; Lockey, James E.; Ehrlich, Rodney I.
Abstract : Background: Continuing use of analog film and digital chest radiography for screening and surveillance for pneumoconiosis and tuberculosis in lower and middle income countries raises questions of equivalence of disease detection. This study compared analog to digital images for intra‐rater agreement across formats and prevalence of changes related to silicosis and tuberculosis among South African gold miners using the International Labour Organization classification system. Methods: Miners with diverse radiological presentations of silicosis and tuberculosis were recruited. Digital and film chest images on each subject were classified by four expert readers. Results: Readings of film and soft copy digital images showed no significant differences in prevalence of tuberculosis or silicosis, and intra‐rater agreement across formats was fair to good. Hard copy images yielded higher prevalences. Conclusion: Film and digital soft copy images show consistent prevalence of findings, and generally fair to good intra‐rater agreement for findings related to silicosis and tuberculosis.